Approximations of classes B^Ω_p,θ of functions of many variables by entire functions in the space L_q (R^d) - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Exact-order estimates are obtained for the best approximations of the classes B^Ω_p,θ of functions of many variables by entire functions of the exponential type in the space L_q (R^d).